Exploring the Relationship between Consumer Behavior and Self-Esteem among Adolescents in Surabaya: Implications for Intervention - Alberto Robinson; Bhanurasmi; Kayshila Saraswati (PELNUS | Pen en Light for Natural Union of Science, 2024)
This study investigates the relationship between consumer behavior and self-esteem among junior high school adolescents in Surabaya, aiming to elucidate the dynamics shaping adolescent development and inform intervention strategies. Utilizing a mixed-method approach, quantitative surveys and qualitative interviews were conducted with a sample of adolescents. The findings reveal significant associations between certain consumer behaviors and self-esteem levels, emphasizing the impact of peer influence and media exposure on adolescents' consumption patterns and self-perceptions. The study underscores the importance of promoting media literacy, critical thinking, and resilience to peer influence in interventions aimed at fostering healthy consumer behavior and positive self-esteem among adolescents. Despite limitations, including the cross-sectional design and sample homogeneity, the study provides valuable insights for educators, parents, and policymakers involved in adolescent development and intervention programs. Further research employing longitudinal designs and diverse samples is recommended to enhance our understanding of these constructs and their implications for adolescent well-being.